6(r+10)=4(8r+2)

Simple and best practice solution for 6(r+10)=4(8r+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(r+10)=4(8r+2) equation:



6(r+10)=4(8r+2)
We move all terms to the left:
6(r+10)-(4(8r+2))=0
We multiply parentheses
6r-(4(8r+2))+60=0
We calculate terms in parentheses: -(4(8r+2)), so:
4(8r+2)
We multiply parentheses
32r+8
Back to the equation:
-(32r+8)
We get rid of parentheses
6r-32r-8+60=0
We add all the numbers together, and all the variables
-26r+52=0
We move all terms containing r to the left, all other terms to the right
-26r=-52
r=-52/-26
r=+2

See similar equations:

| 13x^2+10.5x+10=0 | | -7(a–3)=11–7a | | 67/9=-2+17/3b | | r+7=-4r-1+6r | | 4(5-8x)=-38-3x | | -|x+1|=0 | | x+2/8/9=4 | | a-8=8a+5 | | 2-2c=-3-c | | (N+14)/(4n+6)=3/4 | | x+28/9=4 | | –5q=–10−3q | | -86-45=y | | p2-16p+64=0 | | -14m-15=75 | | 24+8b=b-9 | | -7=x-3x+3 | | -8+9d=8d | | 2x+3=(1x+-1) | | 3(6-4x)=-2 | | V(a)=(8+-2×)(6+-2×)(×) | | -1+6(x-3)=14x+5-8x | | (-2x+3)(6x+5)=0 | | 2=-10a-18 | | 8x+10-4x=46 | | -5/6=-3/4a | | 2+3x.X=5 | | n/14=4.5/7 | | 5(c-6)c=c+11(24) | | 8p-5=-77 | | -15a=165 | | -6x-23=-8 |

Equations solver categories